Factors driving sustainable choice: the case of wine. Issue 3 (7th March 2016) - Sogari, Giovanni; Mora, Cristina; Menozzi, Davide
Abstract : Purpose: – The purpose of this paper is twofold: first, to explore the concept of consumers' perception of sustainable wine and second, to investigate different clusters based on three factors identified (belief about environmental protection, beliefs about sustainable wine certification and attitude towards sustainable-labelled wine) and willingness to pay (WTP). Then, socio-demographic characteristics have been considered to assess whether group's composition differ considerably. Design/methodology/approach: – After preliminary literature review and qualitative analysis through focus groups, data were collected with a web-based questionnaire from 495 Italian wine drinkers. Factor analysis and cluster analysis were carried out using SPSS (21.0) statistical software packages. Findings: – The cluster analysis based on the three factors identified confirms the presence of different segments of consumers. Four groups were identified and named: Well-disposed; Not interested; Skeptical; Adverse. Cluster analysis confirms that consumers with positive attitude towards sustainable wine and higher beliefs of environmental protection (Cluster 1 and 3) have higher WTP for sustainable wine. Research limitations/implications: – One important limitation in the authors study occurred, considering that consumer's answers in a hypothetical environment might not actually reflect the purchase behaviour of consumers in a real situation. Practical implications: – These findings suggest that companies, which are implementing sustainability programmes, should understand what type of consumers value positively the presence of a sustainable claim on the label of a bottle. Originality/value: – The work adds to the literature on wine marketing by evaluating how belief about environmental protection and sustainable wine certification, and attitude towards sustainable wine segment consumers in different groups. Eliciting WTP via hypothetical situation give us a better understanding of these clusters.